Investigation of Genetic Aetiology in Neurodegenerative Ataxias: Recommendations from the Group of Neurogenetics of Centro Hospitalar São João, Portugal - Gomes, Tiago (2017)
In recent decades, a long and increasing list of monogenic neurodegenerative ataxias has been identified, allowing for better characterization of the pathophysiology, phenotype and prognosis of this heterogeneous group of disorders, while also revealing potential new therapeutic targets. However, the heterogeneity and complexity of the genotype-phenotype relationships and the high costs of molecular genetics often make it difficult for clinicians to decide on a molecular investigation based on an unbiased rational plan. Clinical history is essential to guide the diagnostic workup, but often the phenotype does not hold enough specificity to allow for predicting the genotype. The Group of Neurogenetics of the Centro Hospitalar São João, a multidisciplinary team of neurologists and geneticists with special interest in neurogenetic disorders, devised consensus recommendations for the investigation of the genetic aetiology of neurodegenerative ataxias in clinical practice, based on international consensus documents (currently containing potentially outdated information) and published scientific evidence on this topic. At the time these recommendations were written, there were around 10 well described autosomal recessive loci and more than 27 autosomal dominant loci for neurodegenerative ataxias. This document covers, in a pragmatic way, the rational process used for the genetic diagnosis of neurodegenerative ataxias, with specific recommendations for the various groups of these heterogeneous diseases, per the Portuguese reality.